Uji Aktivitas Antibakteri Ekstrak Etanol 70% Daun Ginseng Jawa (Talinum paniculatum (Jacq.) Gaertn) Terhadap Bakteri Shigella dysenteriae - Riwanda Oktaviani; Fitriyanti Fitriyanti; Putri Kartika Sari (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
Shigellosis is a digestive tract infection that can be caused by S dysenteriae bacteria. Javanese ginseng (T. paniculatum (Jacq.) Gaertner) is a plant known to have antibacterial potential. This study aims to determine the content of the class of compounds contained in the 76% ethanol extract of Javanese ginseng leaves and to observe the antibacterial activity of the 70% ethanol extract of Javanese ginseng leaves against S. dysenteriae based on the diameter of the inhibition zone. Antibacterial testing using the disc diffusion method with six variations of extract concentrations including 5%, 10%, 20%, 40%, 60% and 80% for positive and negative controls used Azithromycin 15µg/disk and 0.5% Na-CMC. Identification of the content of secondary metabolites was carried out on alkaloids, phenols, flavonoids, quinones, saponins, steroids/triterpenoids and tannins. The results of the screening test for 70% ethanol extract of Javanese ginseng leaves contained flavonoids, phenols, saponins, steroids and tannins. Antibacterial testing at the smallest concentration, namely 5% of the inhibition zone, is considered weak with an average inhibition diameter of 4.01 mm and at the largest concentration, namely 10%, the inhibition zone is considered strong with an average inhibition zone diameter of 11.26 mm.